Growth Factors in Regeneration and Regenerative Medicine: “the Cure and the Cause” - Kulebyakin, Konstantin Yu.; Nimiritsky, Peter P.; Makarevich, Pavel I. (Frontiers in Endocrinology, 2020)
The potential rapid advance of regenerative medicine was obstructed by findings that stimulation of human body regeneration is a much tougher mission than expected after the first cultures of stem and progenitor cells were established. In this mini review, we focus on the ambiguous role of growth factors in regeneration, discuss their evolutionary importance, and highlight them as the “cure and the cause” for successful or failed attempts to drive human body regeneration. We draw the reader's attention to evolutionary changes that occurred in growth factors and their receptor tyrosine kinases (RTKs) and how they established and shaped response to injury in metazoans. Discussing the well-known pleiotropy of growth factors, we propose an evolutionary rationale for their functioning in this specific way and focus on growth factors and RTKs as an amazing system that defines the multicellular nature of animals and highlight their participation in regeneration. We pinpoint potential bottlenecks in their application for human tissue regeneration and show their role in fibrosis/regeneration balance. This communication invites the reader to re-evaluate the functions of growth factors as keepers of natively existing communications between elements of tissue, which makes them a fundamental component of a successful regenerative strategy. Finally, we draw attention to the epigenetic landscape that may facilitate or block regeneration and give a brief insight into how it may define the outcome of injury.